A homozygous HOXD13 missense mutation causes a severe form of synpolydactyly with metacarpal to carpal transformation. Issue 3 (18th November 2015) - Ibrahim, Daniel M.; Tayebi, Naeimeh; Knaus, Alexej; Stiege, Asita C.; Sahebzamani, Afsaneh; Hecht, Jochen; Mundlos, Stefan; Spielmann, Malte
Abstract : Synpolydactyly (SPD) is a rare congenital limb disorder characterized by syndactyly between the third and fourth fingers and an additional digit in the syndactylous web. In most cases SPD is caused by heterozygous mutations in HOXD13 resulting in the expansion of a N‐terminal polyalanine tract. If homozygous, the mutation results in severe shortening of all metacarpals and phalanges with a morphological transformation of metacarpals to carpals. Here, we describe a novel homozygous missense mutation in a family with unaffected consanguineous parents and severe brachydactyly and metacarpal‐to‐carpal transformation in the affected child. We performed whole exome sequencing on the index patient, followed by Sanger sequencing of parents and patient to investigate cosegregation. The DNA‐binding ability of the mutant protein was tested with electrophoretic mobility shift assays. We demonstrate that the c.938C>G (p.313T>R) mutation in the DNA‐binding domain of HOXD13 prevents binding to DNA in vitro. Our results show to our knowledge for the first time that a missense mutation in HOXD13 underlies severe brachydactyly with metacarpal‐to‐carpal transformation. The mutation is non‐penetrant in heterozygous carriers. In conjunction with the literature we propose the possibility that the metacarpal‐to‐carpal transformation results from a homozygous loss of functional HOXD13 protein in humans in combination with an accumulation of non‐functional HOXD13 that might be able to interact with other transcription factors in the developing limb. © 2015 Wiley Periodicals, Inc.